(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Kierkegaard’s model of despair and its resolution in faith has parallels with how the existential analyst approaches a client who is avoiding awareness of ultimate concerns. This pertains particularly to clients whose romantic heartbreak masks a deeper existential concern.